Comparative efficacy of behavioral despair models in depicting antidepressant-like effect of tramadol - Kumar, Amitabh A.; D, Jayashree; Rajashekar, Sujith Tumkur (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Experimental evaluation of antidepressants (ADs) in diverse animal models is the need of time. There is a constant search for newer models with ease and rapid screening of AD activity. As earlier studies highlight AD effect of tramadol in animal models, the study was undertaken to compare antidepressant-like effect of tramadol in two models of behavioural despair in mice. Methods: Tramadol was administered intraperitoneally (i.p.) at two different doses of 20 and 40 mg/kg, once daily for 7 days to Swiss albino mice. The immobility period of control and drug-treated mice was recorded in tail suspension test (TST) and forced swim test (FST). The antidepressant (AD) effect of tramadol was compared with control (NS) and reference drug imipramine (10 mg/kg, p.o.), administered orally (p.o.) for seven successive days. Results: Tramadol in tail suspension test (TST) produced significant antidepressant effect at 20 and 40 mg/kg doses, as depicted by reduction in immobility period of drug-treated mice compared to control group. The efficacy of tramadol at dose of 40 mg/kg was comparable to that of imipramine treated group (p<0.001). Tramadol in forced swim test (FST) produced significant antidepressant effect only at the dose of 40 mg/kg as compared to control, while the results were insignificant as compared to imipramine treated group (p>0.05). Conclusion: The results of the present study depict antidepressant-like activity of tramadol in both the models of depression TST and FST. But TST in mice seems to be more efficacious in appraising the antidepressant like effect of tramadol.